2016
DOI: 10.1063/1.4968790
|View full text |Cite
|
Sign up to set email alerts
|

A perovskite lead-free antiferroelectric xCaHfO3-(1-x) NaNbO3 with induced double hysteresis loops at room temperature

Abstract: We demonstrated a new CaHfO3-NaNbO3 solid solution system that allows stable antiferroelectric (AFE) (P) phase to exist under ambient conditions. Based on crystal chemistry viewpoint of relative change of the Goldschmidt tolerance factor (t) and polarizability, two new solid solutions were fabricated using the perovskite end member CaHfO3. It was found that the CaHfO3 effectively stabilized the antiferroelectric (AFE) P phase in NaNbO3. In this article, electrical properties and transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 44 publications
3
43
1
Order By: Relevance
“…26 Extensive TEM characterizations in our previous studies have clearly demonstrated that both the FE Q phase and the AFE P phase coexist in pure NN in the virgin state, which was suggested by the electron diffraction pattern analysis that the AFE P phase is present as the predominant phase, together with a small portion of the FE Q phase. [10][11][12]14 The microstructures of NaNbO 3 are shown again in Figs. 2(a) and 2(b).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…26 Extensive TEM characterizations in our previous studies have clearly demonstrated that both the FE Q phase and the AFE P phase coexist in pure NN in the virgin state, which was suggested by the electron diffraction pattern analysis that the AFE P phase is present as the predominant phase, together with a small portion of the FE Q phase. [10][11][12]14 The microstructures of NaNbO 3 are shown again in Figs. 2(a) and 2(b).…”
mentioning
confidence: 81%
“…NaNbO 3 has an AFE P (space group Pbma) phase at ambient conditions; [5][6][7][8][9] however, the double hysteresis loops are rarely observed in NaNbO 3 due to the existence of a metastable ferroelectric (FE) Q (space group P2 1 ma) phase. [10][11][12][13][14][15][16] It is further noted that a stabilized AFE phase requires a lower tolerance factor (t). [16][17][18][19][20][21] The calculation of the Goldschmidt tolerance factor in an ABO 3type perovskite is shown in Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In AFE compounds [3,4], on the other hand, AFE → FE phase transition receives much more attention as AFE domains are nonpolar and do not directly respond to applied fields [5]. Meanwhile, in some AFE materials with certain compositions, both AFE and FE phases can coexist, either in separate grains or in single grains [5,6]. As a result, the electric fieldinduced AFE → FE phase transition occurs more readily, making these compositions suitable for devices such as electrocaloric coolers or electromechanical actuators [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium niobate (NaNbO 3 ) is one of the typical lead-free perovskite structure materials that has attracted significant interest of numerous investigators attributed to its complicated structure and phase transitions. [18][19][20] It is generally believed that NaNbO 3 presents mainly orthorhombic antiferroelectric phase (space group: Pbma) at room temperature and zero electric field. The ferroelectricity of NaNbO 3 can be stabilized by applying high electric field or forming solid solution system, such as NaNbO 3 -LiNbO 3 , NaNbO 3 -KNbO 3 , and NaNbO 3 -BaTiO 3 .…”
mentioning
confidence: 99%